THE EVALUATION OF EIGHT PILLARS TOTAL PRODUCTIVE MAINTENANCE (TPM) IMPLEMENTATION AND THEIR IMPACT ON OVERALL EQUIPMENT EFFECTIVENESS (OEE) AND WASTE - Herry Agung Prabowo; Yudha Bobby Suprapto; Farida Farida (SINERGI, 2018)
In this global era where the level of competition is higher, in addition to the influence of the suitable marketing strategy is also required strategy from the side of production/productivity. PT. XYZ is a company engaged in the manufacturing of snacks especially biscuits. The problem that often occurs in this company is the number of biscuits that are not in accordance with the standard and the production does not reach the target set because the machine suddenly breaks down frequently. To overcome the problems PT. XYZ then choose to implement the Total Productive Maintenance (TPM) strategy. This study aims to evaluate the implementation of 8 TPM Pillars and measure the effects on manufacturing performance in the form of Overall Equipment Effectiveness (OEE) and Waste. This study uses questionnaire-based survey method. The number of samples distributed is 40 units. Which returned and filled 33 questionnaires and which is worth to be processed as many as 30 samples. Then tested the validity and reliability of data using SPSS program. Validity critical value R = 0.361 for n = 30 and error rate 5%. For reliability test, R value = 0.60 was selected. From the validity test, there are 7 items of questions that are not valid so it is not included in the next process. For the reliability test of the questionnaire is quite reliable with the value of Cronbach's alpha of 0.811. From the CFA analysis, only 6 of 8 TPM pillars are significant while for manufacturing performance only OEE variable is significant. Correlation between 8 Pillars of TPM and manufacturing performance is Strong enough with a value of R = 0.862, which also means 74.3% (R2) variable manufacturing performance can be explained/influenced by variable 8 Pillar TPM and 26.7% the rest by other variables.